Advanced asteroseismic modelling: breaking the degeneracy between stellar mass and initial helium abundance - Verma K.; Rørsted J.L.; Serenelli A.M.; Aguirre Børsen-Koch V.; Winther M.L.; Stokholm A. (My University, 2025)
Current stellar model predictions of adiabatic oscillation frequencies differ significantly from the corresponding observed frequencies due to the non-adiabatic and poorly understood near-surface layers of stars. However, certain combinations of frequencies - known as frequency ratios - are largely unaffected by the uncertain physical processes as they are mostly sensitive to the stellar core. Furthermore, the seismic signature of helium ionization provides envelope properties while being almost independent of the outermost layers. We have developed an advanced stellar modelling approach in which we complement frequency ratios with parameters of the helium ionization zone while taking into account all possible correlations to put the most stringent constraints on the stellar internal structure. We have tested the method using the Keplerbenchmark star 16 Cyg A and have investigated the potential of the helium glitch parameters to constrain the basic stellar properties in detail. It has been explicitly shown that the initial helium abundance and mixing-length parameters are well constrained within our framework, reducing systematic uncertainties on stellar mass and age arising for instance from the well-known anticorrelation between the mass and initial helium abundance. The modelling of six additional Kepler stars including 16 Cyg B reinforces the above findings and also confirms that our approach is mostly independent of model uncertainties associated with the near-surface layers. Our method is relatively computationally expensive, however, it provides stellar masses, radii and ages precisely in an automated manner, paving the way for analysing numerous stars observed in the future during the ESA PLATO mission. © 2022 The Author(s) Published by Oxford University Press on behalf of Royal Astronomical Society.